Are Liquidity and Credit Risk Key Determinants of Corporate Credit Spreads (CCS) in India? - B. M., Lithin; Chakraborty, Suman; M. N., Nikhil (Indian Journal of Finance, 2023)
Purpose : The crumble of the financial markets through the recent crises wobbled precariousness in the corporate credit spreads (CCS) critical for risk management and bond pricing. Against this backdrop, this study investigated the role of liquidity and credit risk on CCS. Methodology : The study applied three models using a battery of 392 active corporate bonds in India: pooled OLS, fixed effect, and IV-GMM. Data for the research were collected from Bloomberg and analyzed using Stata. Findings : First, while credit risk did have a role in determining CCS, liquidity holds greater significance as a determining factor. Specifically, there was a 0.9560427 basis point increase in CCS for every basis point increase in bid-ask spread (liquidity). In contrast, CCS increased by 0.3460369 for every basis point increase in credit risk. Second, a negative coefficient for the interaction term between bid-ask spread and credit risk suggested that credit risk was a moderating variable that weakened the relationship between bid-ask spread and CCS. PracticalÂ Implications : The managers should augment their risk management practices to manage liquidity risk better and maintain a higher credit quality to reduce the negative impact of liquidity risk on CCS. Moreover, the findings affirmed that the better the firmâ€™s credibility, the lesser the CCS would be, implying that firms should try to improve their credit ratings. Originality : The results remained consistent across various regression models, and they held significant implications for the literature concerning the modeling of corporate bond prices.